Toys as Mimetic Objects. A Problem from Plato’s Laws - Stephen Kidd (Aisthesis, 2017)
What is a toy? As objects of play, toys seem to be inextricably bound up with mimesis: a child plays ‘make believe’, for example, with a doll or toy cart. But as I will show, Plato has a very different conception of toys from the modern one which tends to conceive of play as essentially mimetic. Toys do not derive their pleasure from being mimetic objects; rather, they are essentially pleasure objects and as such only incidentally mirror the objects of a ‘serious’ or ‘real’ world.